Editorial - Fernández-Arata, Manuel (2018)
Liberabit, Revista Peruana de Psicología presents a new issue consisting of the contributions mentioned hereinbelow. The original articles section begins with the study of Norma Alicia Ruvalcaba-Romero, Mercedes Gabriela Orozco-Solis, Julia Gallegos-Guajardo, and Juan Manuel Nava-Fuerte, professors at a Mexican university, who analyze school relationships, communication with parents, and prosocial behaviors as predictors of positive emotions. The results of this research allow us to conclude that prosocial behaviors and positive bonds with the mother are variables that predict positive emotions in adolescents. Secondly, Valeria E. Moran, Fabián O. Olaz, Edgardo R. Pérez, and Zilda AP Del Prette, authors from Argentina and Brazil, report the production of the Social Anxiety Test for University Students (SAT-U). They found adequate evidence of validity and reliability in the psychometric properties used in the study population. Thirdly, Argentine authors Daniela Alonso and Silvina Brussino study the structure and evidence of validity of the Spanish version of the Psychosocial Values ​​Questionnaire (QVP-24). They adapted the test to the Argentine context, obtaining theoretical and empirical validity. Finally in this section, María Agustina Tuzinkievicz, Nadia Soledad Peralta, Mariano Castellaro, and Cristián Santibáñez, authors from Argentina and Chile, focus on the study of the written individual argumentative complexity of first-year and senior university students. They found a relationship between first-year students and the production of non-argumentative texts, and a relationship between senior students and the production of argumentative texts.